Critiquing Big Data: Politics, Ethics, Epistemology - Crawford, Kate; Miltner, Kate; Gray, Mary L. (International Journal of Communications - Special Section Introduction, 2014)
Why now? This is the first question we might ask of the big data phenomenon. Why has it gained such remarkable purchase in a range of industries and across academia, at this point in the 21st century? Big data as a term has spread like kudzu in a few short years, ranging across a vast terrain that spans health care, astronomy, policing, city planning, and advertising. From the RNA bacteriophages in our bodies to the Kepler Space Telescope, searching for terrorists or predicting cereal preferences, big data is deployed as the term of art to encompass all the techniques used to analyze data at scale. But why has the concept gained such traction now?